Effect of Winter Canola Cultivar on Seed Yield, Oil, and Protein Content. (1st November 2019) - Tetteh, Edmund T.; de Koff, Jason P.; Pokharel, Bharat; Link, Richard; Robbins, Chris
Abstract : Canola ( Brassica napus L.) is an oilseed crop that can produce healthy cooking oil and animal feed byproducts. Although it is a relatively new crop, approved for human consumption less than 40 yr ago, advances in breeding have allowed for its production as a winter crop in the southeastern United States. There is little published research, however, related to its performance and quality in this region. Therefore, a study was conducted during the 2014–2015 (Year 1) and 2015–2016 (Year 2) seasons in Tennessee. Twenty‐three varieties were planted in a randomized complete block design with four replications across both years to determine seed yield, seed oil, and seed protein content. Differences in fertilizer application rates, planting, and harvest management and differences in weather conditions probably led to significant interactions between years. Cultivar yields ranged from 1269 to 2647 and 1494 to 4199 kg ha −1, seed oil content ranged from 44 to 48% and from 43 to 46%, and seed protein content ranged from 20 to 24% and from 19 to 23% for Years 1 and 2, respectively. In each year, open‐pollinated cultivars had significantly lower yield and oil content but significantly greater protein content than hybrid cultivars. There was also a strong negative correlation between seed oil and seed protein and the linear models were significant ( r = 0.88, p < 0.0001 for Year 1; r = 0.85, p < 0.0001 for Year 2). Recommended winter canola cultivars include Exp1302 and Hekip. Core Ideas Little published research is available related to the performance of winter canola in the southeastern United States. Yield, oil, and protein content were identified across 23 potential winter canola cultivars over 2 yr. Significant linear relationships were observed between seed oil and protein content but not when compared with yield.